Lecturers' views of assessment design, marking and feedback in higher education: a case for professionalisation?. Issue 8 (17th November 2019) - Norton, Lin; Floyd, Sarah; Norton, Bill
Abstract: Research on professional assessment practice in higher education does not always take account of lecturers' perceptions and experiences, or their disciplinary context. This questionnaire study was designed to explore lecturers' views about three inter-related elements of professional assessment practice: assessment design, marking and feedback. It consisted of two questionnaires: the Assessment Design Inventory (ADI), previously published, and the Assessment, Marking and Feedback Inventory (AMFI) which was newly developed for this study. The two main purposes of the research were to: i) establish the validity of these two questionnaires as research tools, ii) explore the existence of professional practice in assessment and analyse any perceived hindrances as well as possible effects of participants' subject discipline. 356 lecturers from two UK universities, with a range of teaching experience and representing soft and hard disciplines, took part. Results indicated that the ADI and the AMFI were robust instruments. Findings showed evidence of assessment professionalism, but also some areas where it was lacking, together with a perceived need for formal training. Participants recognised that there were certain hindrances in putting their pedagogical beliefs into practice. The implications of this study are discussed in terms of advancing the sector's understanding of assessment professionalism.